2014
DOI: 10.4274/tjem.2475
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Prognostic Value of TSH Levels in Differentiated Thyroid Cancers

Abstract: Purpose:The frequency of thyroid surgery for suspected malignancy but with a benign result in pathological examination is increasing in recent years. For this reason, additional preoperative markers are needed for increasing the sensitivity for evaluating the preoperative malignancy risk of thyroid nodules. In this study, we aimed to evaluate the diagnostic value of serum TSH levels for determining the differentiated thyroid cancers (DTC) and to identify a proper cut-off value if relevant association is presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…Some studies showed an increased risk of malignancy in a thyroid nodule with high serum TSH, 6,7,30,31 whereas others reported no relationship. 10,[33][34][35] In a meta-analysis including over 5000 cancer preoperatively, an increased level of serum Tg or TSH appear w not to be useful to predict malignant thyroid disorders. However, TSH:Tg ratio was found to be significantly increased in patients with thyroid cancer but it was not shown to be an independent predictor.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed an increased risk of malignancy in a thyroid nodule with high serum TSH, 6,7,30,31 whereas others reported no relationship. 10,[33][34][35] In a meta-analysis including over 5000 cancer preoperatively, an increased level of serum Tg or TSH appear w not to be useful to predict malignant thyroid disorders. However, TSH:Tg ratio was found to be significantly increased in patients with thyroid cancer but it was not shown to be an independent predictor.…”
Section: Discussionmentioning
confidence: 99%